Real-world experience with the IUB Ballerine MIDI copper IUD: an observational study in the French-speaking region of Switzerland. (4th July 2019) - Yaron, Michal; Viviano, Manuela; Guillot, Cecile; Aharon, Arnon; Shkolnik, Ketty
Abstract: Objective: The aim of the study was to assess the acceptability of the intrauterine ball IUB Ballerine MIDI copper intrauterine device (IUD), using real-world data collected from users and physicians. Methods: In this retrospective, observational study, conducted in the French-speaking region of Switzerland, healthy women ( n = 207) who had had an IUB Ballerine MIDI inserted ≥12 months before enrolment, and their physicians completed questionnaires relating to device insertion, user experience and outcome. Questions relating to current menstrual patterns, physical comfort and product satisfaction were only posed to women still using the device. Results: The mean age at insertion was 30.8 ± 7.2 years, with an average 14.2 ± 2.9 month lapse from time of insertion until study commencement. At the time of the study, 140 (67.6%) women were still using the device. The expulsion rate was 5.3% ( n = 11) and the pregnancy rate was 1.4% ( n = 3). Most of the women still using the device reported no to moderate pain or cramps (80.7%). The majority of women reported moderate to high (65.7%) satisfaction with the device, with 81.4% claiming they would recommend it to friends and relatives. Over 84.8% of physicians reported that the device was easy to insert, with no difficulties encountered during the procedure. Conclusions: The IUB Ballerine MIDI was demonstrated to be safe and acceptable in different clinical settings and risk groups among a socioeconomically and demographically diverse study population.